Effectiveness of mHealth interventions for maternal, newborn and child health in low- and middle-income countries: Systematic review and meta-analysis - Siew Hwa Lee1; Ulugbek B Nurmatov 1; Bright I Nwaru 1; Mome Mukherjee 1,2; Liz Grant 3; Claudia Pagliari 1,3 (Edinburgh University Global Health Society, 2016)
Objective: To assess the effectiveness of mHealth interventions for maternal, newborn and child health (MNCH) in low- and middle-income countries (LMIC). Methods: 16 online international databases were searched to identify studies evaluating the impact of mHealth interventions on MNCH outcomes in LMIC, between January 1990 and May 2014. Comparable studies were included in a random-effects meta-analysis. Findings: Of 8593 unique references screened after de-duplication, 15 research articles and two conference abstracts met inclusion criteria, including 12 intervention and three observational studies. Only two studies were graded at low risk of bias. Only one study demonstrated an improvement in morbidity or mortality, specifically decreased risk of perinatal death in children of mothers who received SMS support during pregnancy, compared with routine prenatal care. Meta-analysis of three studies on infant feeding showed that prenatal interventions using SMS/cell phone (vs routine care) improved rates of breastfeeding (BF) within one hour after birth (odds ratio (OR) 2.01, 95% confidence interval (CI) 1.27-2.75, I2=80.9%) and exclusive BF for three/four months (OR 1.88, 95% CI 1.26-2.50, I2=52.8%) and for six months (OR 2.57, 95% CI 1.46-3.68, I2=0.0%). Included studies encompassed interventions designed for health information delivery (n=6); reminders (n=3); communication (n=2); data collection (n=2); test result turnaround (n=2); peer group support (n=2) and psychological intervention (n=1). Conclusions: Most studies of mHealth for MNCH in LMIC are of poor methodological quality and few have evaluated impacts on patient outcomes. Improvements in intermediate outcomes have nevertheless been reported in many studies and there is modest evidence that interventions delivered via SMS messaging can improve infant feeding. Ambiguous descriptions of interventions and their mechanisms of impact present difficulties for interpretation and replication. Rigorous studies with potential to offer clearer evidence are underway.